Prevalence and determinants of left ventricular diastolic dysfunction in obese subjects and the role of left ventricular global longitudinal strain and mass normalized to height. Issue 8 (17th April 2018) - Dini, Frank Lloyd; Fabiani, Iacopo; Miccoli, Mario; Galeotti, Gian Giacomo; Pugliese, Nicola Riccardo; D'Agostino, Andreina; Scartabelli, Alessandra; Conte, Lorenzo; Salvetti, Guido; Santini, Ferruccio; Pedrinelli, Roberto
Abstract : Background: Left ventricular (LV) diastolic dysfunction (DD) is a frequent finding in obesity and may predispose to the development of heart failure (HF). However, no data are available on the prevalence of DD after the introduction of the 2016 Recommendations of the American Society of Echocardiography and the European Association of Cardiovascular Imaging. Methods and results: To assess the impact of the new Recommendations on the prevalence of DD and on their clinical and echocardiographic correlates in obesity, a prospective study was performed in 588 subjects with an ejection fraction (EF) ≥50% and no history of HF either obese (n = 402; mean age: 47 ± 12 years; women 71%; body mass index [BMI]: 44 ± 8 kg/m 2 ), overweight (n = 86; BMI: 28 ± 1 kg/m 2 ), or with a normal weight (n = 100; BMI: 22 ± 2 kg/m 2 ). All subjects underwent an echocardiographic and Doppler study, including the assessment of global longitudinal strain (GLS). DD occurred in 19% of obese patients, 12% of overweight subjects, and 2% of normal weight subjects. We used multivariable logistic analysis to assess the risk of DD. In patients with BMI ≥30 kg/m 2, LV mass normalized to height (2.7) (OR: 1.04, P = .0028), and GLS (OR: 0.85, P = .0032) were associated with an increased risk of DD followed by EF (OR: 0.91, P = .045), diabetes (OR: 1.91, P = .065), and systolic blood pressure (OR: 1.02, P = .076). Conclusion: These results show that DD is highly prevalent among obese subjects and impairment of longitudinal systolic mechanics, as reflected by GLS reduction, and LV mass normalized to height are major independent predictors of DD in this patients' population.